Women’s Counter-Memories of the First War World: two emblematic case–studies Vera Brittain, Mary Borden - Fortunati, Vita (Cadernos de Literatura Comparada, 2014)
The tradition of canonical war writing has long been seen as something belonging to men, on the contrary, for many women the First World War was a sort of catalyst for developing a public voice while at the same time creating a different gender perspective on the same historical event. This aspect has become evident since the last two decades of the Twentieth Century when cultural historians, Memory Studies and Gender Studies pointed out not only the inadequacy of a monolithic memory but also the many traces left by women’s controversial memories of the same event in the collective consciousness. In this perspective the numerous European female writings (especially memoirs and autobiographies) show the extent to which First World War turned upside down the relationships of individuals with the ‘symbolic order’ in which they have grown up. The outpouring of European female writing reveals both the impact war had on women in finding new social roles and their different political positions in European woman’s suffrage movement. For instance in England in the women’s movement for the vote, First World War provoked the break between the pacifist Sylvia Pankhurst and her mother, the well-known leader of the Women’s Social and Political Union. Particularly interesting, as Vera Brittain shows in her moving autobiography Testament of Youth, is the way the danger threatening the homeland led to the apparent negation of the traditional view of opposing male and female roles and positions in the society, resumed, nevertheless, later at the end of the war. Our paper will highlight some of the many thorny issues war female writings arise with particular regards to English historical context and to same case- studies such as Vera Brittain and Mary Borden’s works.